LEADERSHIP IN COPE WITH PROSTITUTE IN SOCIAL DEPARTMENT OF BANDAR LAMPUNG - Ida Farida; Refly Setiawan (University of Sang Bumi Ruwa Jurai, 2018)
Leadership is a way of leading where there are aspirational forces, creative forces and moral strength that can influence members to change attitudes, so they become aware of the leader's desires. The existence of leadership Social Department of Bandar Lampung is need of its role because the level of prostitution in the city of Bandar Lampung is increasingly pathetic, this is in serious condition by the level of prostitution contained in the city of Bandar Lampung.The method used in this research is qualitative data analysis. Where researchers are directly involved to obtain data from the beginning to the end of the study. Sources and types of data used are primary data and secondary data. Based on data analysis that has been done, Leadership in tackling problem of prostitute at Social Service of Bandar Lampung city less effective run seen in less the unevenness of rehabilitation program for prostitute woman, lack of manpower of society, lack of job field and lack of complete facilities and infrastructure to support the ability of prostitutes.